“Laudatio et Gratitude”. To Lester E. Embree, for his Worth as a Person, as a Leader and as a Phenomenologist - Pintos Peñaranda, Maria Luz (Investigaciones Fenomenológicas, 2021)
Insight into Lester Embree’s C.V. Recovery and recognition of his inner purpose with regard to his critical detachment from a particular orientation of phenomenology. Phenomenological theory only makes sense as prepa-ration for real practice. When did the view that we, the “soi disant” phenomenologists, are far from the genuine practice of phenomenology arise in Embree? And, who inspired him, apart from Husserl himself? These are key questions to understand unity and inner coherence in Embre’s C.V., and they meet two aims. The first one is to find the link between his initial entry in phenomenology and his critical stance, particularly evident in the last two decades of his life. The second one is to identify who could have been his guide and model‒apart from Husserl‒from the beginning of his life as phenomenologist until his last two decades, when he wrote his comments on pseudophenomenology. In any case, Embree has been a critical voice who compels us to think about the orientation we are giving to the phenomenology inherited from Husserl. He is therefore a brave and honest philosopher, full of great humanity. In addititon to these qualities, it is worth noting both his creative intelligence and foresight to see‒earlier than others‒the evolution followed by phenomenology until now and his valuable multidisciplinary contribution. Praise to Lester Embree. Mirada hacia el interior del C.V. de Lester Embree. Recuperación y reconocimiento de su propósito interno con respecto a su distanciamiento crítico hacia cierta orientación de la fenomenología. La teoría fenomenológica únicamente tiene sentido como preparación para una real práctica. ¿Cuándo emerge en Embree su consideración de que los “soi disant” fenomenólogos estamos alejados del verdadero ejercicio de la fenomenología? Y, ¿en quién se inspira él además de en Husserl? Estas preguntas son importantes para entender la unidad y coherencia internas en el C.V. de Embree y sirven para satisfacer dos objetivos. El primero es hallar un vínculo entre su entrada inicial en la fenomenología y su posicionamiento crítico manifiesto especialmente en las últimas dos décadas de su vida. El segundo objetivo es determinar quién pudo actuar para él —además de Husserl— como guía y modelo desde el comienzo de su vida de fenomenólogo hasta esas dos últimas de su vida en las que escribe sus comentarios sobre la pseudofenomenología. En todo caso, Embree es una voz crítica que nos fuerza a pensar acerca de la trayectoria que nosotros estamos dando a la fenomenología heredada de Husserl. Él es, así, un filósofo valiente y honesto y de una gran humanidad. Se unen a estas cualidades su gran inteligencia creativa y su sorprendente perspicacia para ver —antes que otros— la evolución que ha seguido la fenomenología hasta hoy y la valiosa contribución multidisciplinar actual. Alabanza a Lester Embree.